RANCANG BANGUN SISTEM INFORMASI PEMESANAN RUANG PADA KARAOKE INUL VIZTA THAMRIN BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract - InulViztaThamrin is a family karaoke place, where many people took the time to sing with the family. Since the number of customers InulVizta then provided a karaoke room booking so that customers do not have to queue when they want to sing. At karaoke InulViztaThamrin in Semarang has been built applications Web based karaoke room reservation. In this system, the authors utilize a web application that is by ordering online.The purpose of this research is to make the information system web based karaoke room reservations, where customers InulVizta can make reservations online space, this system was made in order to facilitate customers in the karaoke room reservation. The programming language used in designing this system is PHP,and writer for data storage using MySQL,as well as supporting programs using AppServ, for methods development of this system is the method of prototyping.Results from this system, customers will be easy to book a room karaoke with time and space in accordance with the wishes and are needed by the customer. Keywords - Space, Karaoke, Booking, Web-Based Information System.